From Scientific Research to Geoconservation and Geopark - Dan Grigorescu (Geoconservation Research)
The Haţeg region of Transylvania-Romania, known as the “Haţeg Country”, due to its specific character as a region wholly encircled by mountains, has been renowned for over a century for its palaeontological geosites from which dinosaur bones of several species, dinosaur eggs and hatchlings, were unearthed along with numerous other taxa representative of all the major vertebrate groups: fishes, amphibians, reptiles, birds and mammals. The region illustrates the phenomenon of “insular dwarfism”, linked to the lengthy persistence of animals in isolated habitats. Palaeontological research in the region took place across two periods, separated by a 50-year gap in which no systematic studies were carried out. The first, closely associated with Franz Nopcsa, spanned between 1897 and 1929; the second period, begun in 1977, continues to this day. The main achievements of these two periods are briefly presented. After 1990, the region also became a centre for geoconservation, incorporating a complex activity of research, protection and valorisation of existing dinosaur sites, under the tutelage of geologists from the University of Bucharest. These efforts led to UNESCO recognizing the region as the “Haţeg Country Dinosaurs Geopark” in 2005. Afterwards, it became a leading centre for geoeducation and geotourism in Romania. Here, we discuss the roles played in this achievement by enduring scientific research in the fields of geology and palaeontology across the region, the efforts for the geoconservation of the fossiliferous sites and not least local authorities’ involvement and cooperation.